Formal Languages and Automata Theory - Anami, Basavaraj S. (Wiley India, 2012)
This book presents the theoretical aspects of Computer Science. This subject explains how to define infinite languages in finite ways, construct algorithms for related problems and decide whether a string is in language or not. This book adopts a holistic approach to learning.